2022
DOI: 10.1017/s1537592722001074
|View full text |Cite
|
Sign up to set email alerts
|

From “Freedom Now!” to “Black Lives Matter”: Retrieving King and Randolph to Theorize Contemporary White Antiracism

Abstract: Many were taken aback by the initial spike in support for Black Lives Matter among white Americans during the summer of 2020. But will these antiracist attitudes translate into antiracist behavior? Accordingly, I ask under what conditions do white Americans engage in antiracist behavior? To answer this question, I build upon the insights of Martin Luther King, Jr., and A. Philip Randolph to theorize contemporary white antiracism. I argue that, under neoliberal capitalism, the conditions they laid out as necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…While we do find that support for race-based policies designed to redress racial inequalities increases after exposure to a story about race that frames inequality as structural, it is unclear how long these effects would last. Further, even if the attitudinal changes did last, it is unclear, and perhaps even unlikely, that such attitudes would translate into behavior (Clemons, 2022). This tends to be a shortcoming of experimental studies-especially those embedded in surveys-as resources often prevent substantial follow-up contact with participants and surveys do not lend themselves to behavioral tests.…”
Section: Discussionmentioning
confidence: 99%
“…While we do find that support for race-based policies designed to redress racial inequalities increases after exposure to a story about race that frames inequality as structural, it is unclear how long these effects would last. Further, even if the attitudinal changes did last, it is unclear, and perhaps even unlikely, that such attitudes would translate into behavior (Clemons, 2022). This tends to be a shortcoming of experimental studies-especially those embedded in surveys-as resources often prevent substantial follow-up contact with participants and surveys do not lend themselves to behavioral tests.…”
Section: Discussionmentioning
confidence: 99%
“…This perspective recognizes the class distinctions among racialized groups without discounting the impact of racial discrimination on all youth of color (Leonardo, 2012). From this view, the addition of class to CRSE would complement the focus on racial inequality and eschew color-blind approaches that neglect the impact of race (Bonilla-Silva, 2006;Clemons, 2022). A class-informed approach to CRSE could also help fulfill the aim of promoting critical consciousness in students by exploring ways in which race has historically been used to undermine and obscure class solidarity (Haney López, 2019;Roediger, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In what follows, I draw upon research that has demonstrated the salience of class among racially minoritized populations and argue that an approach that accounts for the confluence of class and race would be a fruitful addition to CRSE scholarship and practice. The addition of a class-oriented lens to CRSE would complement rather than displace its traditional emphasis on race (Bonilla-Silva, 2006;Clemons, 2022).…”
Section: Class Race and Crsementioning
confidence: 99%
“…Dovetailing with a literature that argues that voters with more education and more income are more likely to hold more socially/ culturally liberal views than other voters (e.g., Inglehart 1981;Broockman, Ferenstein, and Malhotra 2019) which may even be more likely than their economic views to drive their voting behavior (Enke, Polborn, and Wu 2022), many scholars agree that many more Americans today simply hold more socially/culturally liberal views than ever before. One likely crucial element to the increase in socially/culturally liberal voters is the increasing (although still minority) shares of Black, Latino, and other voters of color earning relatively high incomes (e.g., figure 4), in addition to the decrease in white Americans expressing "racially resentful" views-which are symbolic and do not necessarily imply concrete economic policy preferences-over time (Clemons 2022). These various interrelated forces shaping the social/cultural views of many affluent voters, in particular, very likely drive more of them to feel more allegiance to the Democratic over Republican Party, as there is clear polarization between the parties on these issues.…”
Section: Why Have Affluent Americans Swung Democratic?mentioning
confidence: 99%